Isolation of Indigenous Phytophthora palmivora from Indonesia, Their Morphological and Pathogenecity Characterization - Rubiyo Rubiyo; Agus Purwantara; Sri Sukamto; Sudarsono Sudarsono (Indonesian Coffee and Cocoa Research Institute, 2008)
AbstractThis experiment aims to know the solar energy efficiency of four clones of cocoa that cultivated under three different shading plants. This experiment has been done from September until December 2013 located at Kaliwining Experiment Farm with characteristic 45 m above sea level, soil type is low humic gley, soil texture is silty clay loam, and climate classification type D based on Scmidht and Fergusson Classification. This experiment used Nested Design as Experimental Design with species of shading plant as main plot which are Teak (Tectona grandis L.), Krete (Cassia surattensis (Burm.) F.), Lamtoro (Leucaena leucocephala L.) and Cocoa clones as sub plot which are Sulawesi 1, Sulawesi 2, KKM 22, KW 165. The observation of solar energy efficiency consists of daily solar radiation intensity, solar radiation intensity above plant, solar radiation intensity under plant, and also plant total dry weight. The experimental result showed that there is differences (heterogenity) between shading location based on homogenity test by Bartlett Method. There are some interaction between the kind of shading plant and clones in parameter of interception efficiency, absorbtion efficiency, the efficiency of solar energy that caught by plant, and solar energy conversion efficiency. The efficiency of solar energy that caught by plant will affect the solar energy conversion efficiency with R2 = 0,86. Keywords : Solar Energy Efficiency, Cocoa Clones, Shading Plant, Nested Design, Bartlett Method